Development of Palventure Board Game Service Media for Improving Attitudes to Antibullying - Hutagaol, Vanessa Br.; Suwarjo, Suwarjo (FKIP - Universitas Riau, 2025)
Board games provide a safe and controlled simulation of reality, allowing individuals to explore roles and understand the consequences of their behavior. At the same time, the case of bullying, which is quite prevalent in the school environment, is another concern for teachers. The purpose of this research is to produce a board game that is feasible, practical, and effective in improving attitudes towards antibullying.This research was a type of research and development that used the model of Borg and Gall. The effectiveness of the product was tested using a t-test. The results of this study are: (1) products in the form of board game Palventure with components namely the game board, cards, dice, pawns, and tokens where the game mechanics are arranged in a manual; (2) board game Palventure declared very valid with a score of 92% from guidance and counseling service experts and 88% from media experts; and (3) board game PALVENTUREdeclared very practical by guidance and counseling teachers with a score of 83%, (4) board game Palventure is found to be effective in improving attitudes towards antibullying with a P-value of 0.002 (<0.05).